Nyai's Representation in Bumi Manusia Film (Analysis of Semiotics of Bumi Manusia Films) - Shinta Dwi Andriani Budiartho; Poppy Febriana (Indonesian Journal of Cultural and Community Development, 2021)
Nyai's Reception at Bumi Manusia (Semiotic Analysis of Cristian Metz Film) This thesis has not been published. Faculty of Business, Law and Social Sciences. Muhammadiyah University of Sidoarjo. This study aims to find out the content of the written film contains many sets of signs and needs to be understood so that a message conveyed by the film director is right on target. The film Bumi Manusia is the object of this research, there is a Nyai character who lifts the success of this film. Nyai has a certain connotation and stigma, which in the Big Indonesian Dictionary is translated as a call intended for women who are not or are already married. Nyai is the same as concubine. That's what makes researchers intrigued to examine the role of Nyai Ontosoroh in the film Bumi Manusia entitled "Representation of Nyai on Earth of Mankind". The researcher uses a descriptive qualitative method which is then analyzed using the theory of Semiotics. Chistian Metz's film has several syntagmatic types, but in this study only eight types of syntagmatic are used, namely Bracket Syntagma, Sequences, Descriptive Syntagma, Scene, Autonomous Shot, Narrative Syntagma, Episodic Sequence. Then, it is perceived using Gayatri Spivak's theory of Postcolonialism against the Subalterns. Spivak's opinion is that the position of indigenous women is a subaltern group because of the dominance of the male group. Nyai as subalterns are disadvantaged, in terms of honor, self-respect and their right to be a mother.